Influence of the viscoelastic regime onto the UV reactivity of poly(lactic acid). (January 2019) - Marek, Adam A.; Verney, Vincent
Graphical abstract: Highlights: The photochemical reactivity of PLA in the rubbery and molten state is exemplified. PhotoRheology and photoDSC are used to determine the reactivity of PLA. The photochemical reactivity of PLA depends on viscoelastic state. The influence of hydroperoxides on the evolution on Tg for PLA is discussed. Abstract: The photochemical reactivity of poly(lactic acid) in the rubbery and molten state was determined by two methods: photoRheology and photoDSC. Significant changes in rheological behaviour of PLA were observed, depending on the viscoelastic regime. In the rubbery state, cold crystallization causes difficulties in oxygen diffusion resulting mainly in crosslinking reactions. In the molten state, the competition between crosslinking and degradation was observed due to hydroperoxides decomposition. In all cases UV irradiation intensifies the reactions. Using PhotoDSC we determined the effect of hydroperoxides on the PLA degradation process, and the difference in effectiveness of temperature and UV on hydroperoxides decomposition.